2012
DOI: 10.1097/bsd.0b013e318213c113
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Kyphoplasty and Vertebroplasty for Treatment of Painful Osteoporotic Vertebral Compression Fractures

Abstract: Kyphoplasty and vertebroplasty demonstrated similar good clinical outcomes during the 12-month follow-up. Kyphoplasty offers a higher degree of spinal deformity correction and results in less cement leakage than vertebroplasty. The benefits of these relative merits need to be ascertained in future long-term studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 45 publications
3
56
2
Order By: Relevance
“…6,44,45 With KAVIAR, 75% of patients with VP had postural reduction, accounting for deformity correction in the VP group, and this finding may explain less postoperative correction in VP (compared to BKP) reported in other studies. 8,40,41 The subsequent radiographic fracture rate is similar to that in another RCT 5,10 and is likely due to the high number of prevalent fractures at baseline, a potent risk factor. 13 This finding underscores the importance of additional therapeutic measures such as pharmacologics to help reduce fracture risk.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…6,44,45 With KAVIAR, 75% of patients with VP had postural reduction, accounting for deformity correction in the VP group, and this finding may explain less postoperative correction in VP (compared to BKP) reported in other studies. 8,40,41 The subsequent radiographic fracture rate is similar to that in another RCT 5,10 and is likely due to the high number of prevalent fractures at baseline, a potent risk factor. 13 This finding underscores the importance of additional therapeutic measures such as pharmacologics to help reduce fracture risk.…”
Section: Discussionmentioning
confidence: 57%
“…8 Nonrandomized comparisons show similar results. 40,41 Here, postsurgery kyphotic angulation correction was similar between groups. There was some loss of correction in both groups at 3 months; however, for VP, the trend was more loss, with a statistically significant 24-month difference between groups (Table 3).…”
Section: Discussionmentioning
confidence: 87%
“…Of the remaining 187 citations, case series, review articles, publications describing novel basic technologies, and technique reports were eliminated. The remaining 14 studies, including 7 systematic reviews [18][19][20][21][22][23][24] and 7 controlled studies, [25][26][27][28][29][30][31] were saved and reviewed. The selection process is described in Figure 6.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] KP is a treatment procedure that was developed with the expectation that it would provide better resolution of vertebral deformities than VP because of the insertion and inflation of a balloon within the collapsed vertebral body. Although some reports show that the postoperative height restoration and kyphotic changes achieved by KP are significantly superior to those achieved by VP, [10][11][12][13] others report scarce differences in these outcomes between balloon KP and VP, [14][15][16] and no consensus has yet been reached. It has been reported that the presence of vertebral mobility associated with pseudoarthrosis of the fractured vertebral bodies greatly influences the postoperative height restoration and kyphotic changes after conventional VP [17][18][19][20] ; however, the influence of vertebral mobility on the outcomes of KP has been studied very little.…”
mentioning
confidence: 99%